2010
DOI: 10.1007/s12540-010-0407-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study on the wear behavior of long and short glass fiber reinforced plastics

Abstract: In recent years, the fiber reinforced composites have been used more in tribological applications where the sliding surfaces requires a high wear resistance and a low co-efficient of friction. The growth of GFRP is significantly higher than that of steel. No engineer or designer can ignore the growth of GFRP, but the decision to use a new material is difficult, yet important. The comparative tribological performance of short and long glass fiber-epoxy composites, under varying load and sliding velocities, is r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Glass fiber-reinforced plastic (GFRP) is the cheapest and widely used composite in industrial applications [1][2][3][4][5]. Generally, there are two kinds of glass fibers, short glass fibers (SGF) and long glass fibers (LGF).…”
Section: Introductionmentioning
confidence: 99%
“…Glass fiber-reinforced plastic (GFRP) is the cheapest and widely used composite in industrial applications [1][2][3][4][5]. Generally, there are two kinds of glass fibers, short glass fibers (SGF) and long glass fibers (LGF).…”
Section: Introductionmentioning
confidence: 99%
“…The GF/PI exhibited the highest elastic modulus and hardness among these PI composites. This fact indicated that the GF had a better reinforcement effect on PI because of its excellent mechanical properties and load capacity [21,22]. Besides, the modulus and hardness played an important role on the friction and wear behaviors of the same materials under the same testing condition (see next discussion).…”
Section: Characterizationmentioning
confidence: 85%
“…The aim of reinforcements in composites are to get strength, stiffness and other mechanical properties, dominate other properties as coefficient of thermal extension, conductivity and thermal transport. Composite materials can be classified in different ways [5]. Classification based on the geometry of a representative unit of reinforcement is convenient since it is the geometry of the reinforcement which is responsible for the mechanical properties and high performance of the composites.The two broad classes of composites are.…”
Section: Introductionmentioning
confidence: 99%